2012
DOI: 10.1097/aud.0b013e31825f9d89
|View full text |Cite
|
Sign up to set email alerts
|

Digital Music Exposure Reliably Induces Temporary Threshold Shift in Normal-Hearing Human Subjects

Abstract: Objectives One of the challenges for evaluating new otoprotective agents for potential benefit in human populations is availability of an established clinical paradigm with real world relevance. These studies were explicitly designed to develop a real-world digital music exposure that reliably induces temporary threshold shift (TTS) in normal hearing human subjects. Design Thirty-three subjects participated in studies that measured effects of digital music player use on hearing. Subjects selected either rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 84 publications
8
91
0
2
Order By: Relevance
“…If current data are indicative of an attentional mechanism, then these results could provide a partial explanation as to why some animals experience tinnitus after the same noise-induced hearing loss whereas others do not. That the perception and sensation of tinnitus varies across individuals exposed to identical noise conditions is clear (Le Prell et al 2012;Spankovich et al 2013). Perhaps, it is the abnormal gating, in addition to the degree of cochlear damage that results in the tinnitus percept (Zhang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If current data are indicative of an attentional mechanism, then these results could provide a partial explanation as to why some animals experience tinnitus after the same noise-induced hearing loss whereas others do not. That the perception and sensation of tinnitus varies across individuals exposed to identical noise conditions is clear (Le Prell et al 2012;Spankovich et al 2013). Perhaps, it is the abnormal gating, in addition to the degree of cochlear damage that results in the tinnitus percept (Zhang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are more prone to TTS might also be more prone to NIPTS (Feuerstein et al 2014;Moshammer et al 2015), and remediation of TTS by a therapeutic might also indicate promise against NIPTS (Le Prell et al 2012;Le Prell and Lobarinas 2015). In addition, the recent surge of interest in hidden hearing loss and Bsynaptopathy^has heightened interest in TTS as a risk factor for primary neural loss.…”
Section: The Meaning and Significance Of Ttsmentioning
confidence: 99%
“…Le Prell et al (2012) found no left-ear differences in their experiment where 33 subjects were exposed to 94, 98, and 100 dB (A). They found the largest TTS at 2000 -6000 Hz.…”
Section: Observed Effectsmentioning
confidence: 92%
“…The (high) exposure levels that were studied resulted in TTS of approximately 40 dB. Le Prell et al (2012) noted that ' The TTS threshold below which there is no lasting synaptic change is not known, and should there be any new evidence which suggests that even a small TTS that rapidly recovers is harmful, studies such as these would not be possible. '…”
Section: S47mentioning
confidence: 96%